Implementasi Market Day dalam Meningkatkan Kemampuan Berhitung Anak Usia Dini: Studi Kualitatif di TK Panti Asih Banjarejo - Siti Diastutik; Latifatus Sa'adah; Helina Himmatul Ulya Lina (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Tarbiyah dan Keguruan, Universitas Islam Bandung., 2025)
This study aims to examine the effectiveness of Market Day activities in improving early childhood numeracy skills. The research employed a descriptive qualitative approach with 30 Group B students at TK Panti Asih Banjarejo as the subjects. The findings indicate an improvement across all indicators, as reflected in the increasing number of children who were able to apply simple operations, count money accurately, differentiate product prices, and demonstrate greater independence and more mature communication skills. Market Day provided an authentic learning experience that strengthened numeracy concepts while simultaneously fostering children's social–emotional development. The study recommends implementing Market Day on an ongoing basis, accompanied by evaluations of numeracy development as a contextual learning strategy. Practically, teachers can utilize simulation-based transaction activities to build more meaningful numerical understanding; Theoretically, these findings support constructivist learning approaches in early childhood education.